White blood cell recovery after allogeneic hematopoietic cell transplantation predicts clinical outcome. Issue 6 (3rd March 2014) - Kim, Haesook T.; Frederick, David; Armand, Philippe; Andler, Emily; Kao, Grace; Cutler, Corey; Koreth, John; Alyea, Edwin P.; Antin, Joseph H.; Soiffer, Robert J.; Ritz, Jerome; Ho, Vincent T.
<x xml:space="preserve">Abstract</x> To determine whether outcome after allogeneic hematopoietic cell transplantation (HCT) could be estimated by using peripheral white blood cell count (WBC) as a metric that integrates several aspects of HCT recovery, we conducted a retrospective study of 1, 109 adult patients who underwent first allogeneic HCT from 2003 through 2009. WBC at 1–3 months after HCT was categorized as low (<2), normal (2–10), and high (>10 × 109 cells/L). Overall survival (OS) and progression‐free survival (PFS) were lower for patients with low or high WBC at 1–3 months after HCT (P < 0.0001). We developed a predictive three‐group risk model based on the pattern of WBC recovery early after HCT. Five‐year OS was 47, 30, and 15% (P < 0.0001) and 5‐year PFS was 39, 22, and 14% for patients in the three different risk groups (P < 0.0001). The pattern of WBC recovery early after HCT provides prognostic information for relapse, nonrelapse mortality, progression‐free survival, and overall survival. A scoring system based on the trajectory of the WBC in the first 3 months after HCT can effectively stratify patients into three groups with different PFS and OS. If validated, this system could be useful in the clinical management of patients after HCT, and to stratify patients enrolled on HCT clinical trials. Am. J. Hematol. 89:591–597, 2014. © 2014 Wiley Periodicals, Inc.